Gabinetes de prensa como principal fuente documental de los medios de comunicación. Fuenlabrada como caso de estudio - Catalina García, Beatriz (2015)
The routines documentaries of professionals working in the press offices of any public or private entity have changed extraordinarily with adaptation of the tools available on the Internet. These alterations have dramatically impacted the provision of information to various media: the generated files in the cabinet, mostly press releases, are submitted in online format. In this article are analyze the relation among local media and press office of the City of Fuenlabrada. Through monitoring and content analysis of the news published in local media, this paper therefore seeks to ascertain the acceptance or rejection of the information generated by this institution and proposals for publication in different media. As a complementary purpose and by means of a structured questionnaire, are analyzed the relations between local journalists and the press office professionals. Among the most important findings, is observed a clear trend to consider the city hall as their main source of information with a remarkable adoption of institutional information on the content of the different media.